SEISMIC GEOMORPHOLOGY AS A TOOL FOR RESERVOIR CHARACTERIZATION: A CASE STUDY FROM MORAGOT FIELD OF PATTANI BASIN, GULF OF THAILAND - Shakhawat Hossain (Malaysian Journal of Geosciences, 2019)
Pattani Basin hosts the greatest number of hydrocarbons producing fields in the Gulf of Thailand. Early to Middle Miocene fluvial channel and overbank sands are the main reservoirs in this basin. Due to their nature of very limited vertical and horizontal distribution it is not always easy to predict the geometry and distribution of these sands based on the conventional seismic interpretation. This study aims to study seismic geomorphology at different stratigraphic intervals to predict sand distribution by applying advanced imaging techniques such as RMS amplitude analysis, spectral decomposition, semblance and dip steered similarity. For this purpose, the study interval is divided into three periods. In period 1, RMS and semblance successfully identified sand bodies and mud filled channels associated with channel belts. On the other hand, deeper stratigraphic levels (period 2 & 3) can be imaged more effectively by using spectral decomposition and dip steered similarity volumes. Horizon slices from these attribute volumes show the distribution of sands and mud filled channels at different stratigraphic level. The width of channel belts varies from 200 m to 3 km. These channel belts are N-S and NW-SE oriented. The findings from seismic geomorphology analysis in these three (3) periods were then validated by well log analysis and correlation. Broad channel belts in horizon slices in period 3 correspond to stacked channel sands in well log. Whereas narrow channel belts correspond to thin sand units in well log in period 2. Widespread occurrence of coals has also been noticed in this interval. Very well-developed meander belts in horizon slices are transpired as fining upward succession in well logs in period 1. Mud filled channels identified in the horizon slices might act as a barrier and compartmentalize the reservoir. The proposed workflow of predicting sand distribution in this study might help to reduce exploration risk as well as in planning infill development wells.